117 Impact of Antipsychotic Treatment Switching in Patients with Schizophrenia, Bipolar Disorder, and Major Depressive Disorder. (April 2020) - Ayyagari, Rajeev; Thomason, Darren; Mu, Fan; Philbin, Michael; Carroll, Benjamin
Abstract: Study Objective: To evaluate the risk of relapse for patients with schizophrenia (SZ), bipolar disorder (BP), and major depressive disorder (MDD) who switched antipsychotics compared with those who did not switch. Background: Antipsychotics are commonly used for maintenance treatment of SZ, BP, and MDD but can have significant side effects, such as extrapyramidal symptoms (EPS). Adherence to treatment is important for reducing the risk of relapse, but fear of side effects may prompt medication switching. Methods: Medicaid claims from 6 US states spanning 6 years were retrospectively analyzed for antipsychotic switching versus non-switching. For all patients with SZ, BD or MDD and for the subset of patients who also had ≥1 EPS diagnosis during the baseline period, times to the following outcomes, during a 2-year study period were analyzed: underlying disease relapse, psychiatric relapse, all-cause emergency room (ER) visit, all-cause inpatient (IP) admission and EPS diagnosis. Results: Switchers (N=10, 548) had a shorter time to disease relapse, other psychiatric relapse, IP admissions, ER visits, and EPS diagnosis (all, log-rank P<0.001) than non-switchers (N=31, 644). Switchers reached the median for IP admission (21.50 months) vs non-switchers (not reached) and for ER visits (switchers, 9.07 months; non-switchers, 13.35 months). For disease relapse, other psychiatric relapse, and EPS diagnosis, <50% of patients had an event during the 2-year study period. Comparisons in a subgroup of patients with ≥1 EPS diagnosis revealed similar outcomes. Conclusions: These results show that disease and other psychiatric relapse, all-cause ER visits, IP admissions, and EPS diagnosis occurred earlier for switchers than for non-switchers, suggesting that switching is associated with an increased risk of relapse in patients with SZ, BP and MDD. Funding Acknowledgements: This study was supported by Teva Pharmaceuticals, Petach Tikva, Israel.